Research progress on application of dental stem cells in alveolar bone and periodontal regeneration - Zhaoyong Liu; Chengbin Guo; Jing Guo; Shan Huang; Peng Du (MedComm – Future Medicine, 2024)
Abstract Periodontal disease is a prevalent inflammatory condition affecting the tissues and bone surrounding the teeth, posing significant challenges to oral health. Current treatments often fall short due to incomplete removal of bacteria and plaque, irreversible damage to gums and bone, and their cost and time‐consuming nature. Stem cell therapy offers a promising alternative that potentially addresses these limitations. This review delves into the biology, mechanisms, and applications of dental stem cells (DSCs) in alveolar bone and periodontal regeneration. We begin with an overview of various stem cell types and their characteristics, highlighting their role in tissue regeneration and the mechanisms involved. Subsequently, we examine preclinical and clinical studies that demonstrate the efficacy and safety of DSC therapy, showcasing their potential in restoring periodontal health. The discussion also extends to the critical challenges and future directions in the field, emphasizing the necessity for standardized protocols and rigorous research to fully integrate DSC‐based therapies into routine clinical practice. This review underscores the transformative potential of DSCs in regenerative dentistry, aiming to provide a comprehensive understanding that can propel further advancements and ultimately improve patient outcomes in periodontal therapy.